Effectiveness and safety of inhaled corticosteroid therapy in asthmatic children and adolescents (Research, Society and Development, 2021)
The aim of this study was to investigate the use of inhaled corticosteroids (IC) for the treatment of asthma in order to provide relevant information and ensure a safer and more effective treatment for children and teenagers. An systematic review of the literature available on PubMed, Scielo and ScienceDirect was carried out using the following the descriptors: asthma, corticosteroids, drug therapy and children.The selected works were: open access; published in either Portuguese, English or Spanish; ranging from the year 2016 to 2021. Of the 233 compiled studies, 14 were selected. In the research, it was noticed that the particle size has an influence in the effectiveness and safety of the treatment, changing the availability of the drug in its target and the dosage administered to promote the desired effect. Furthermore, the particularities of ICs available on the market, which can be used alone or in combination with β2-adrenergic agonists, allow for a reduction in the IC dosage, thus reducing the incidence of possible adverse drug reactions (ADRs). It is important to emphasize that fluticasone proved to be one of the safest medications when its influence in the growth of children and adolescents was considered. Finally, despite the range of studies in the area, further research on this topic is necessary, especially those involving the influence of particle size on the effectiveness and safety of treatment, as well as the main ADRs on the proposed topic.